Golden jubilee for an iconic financial formula - Horvath, BN (Springer Nature, 2023)
Fifty years ago, an equation called the Black–Scholes formula revolutionized finance, leading to a rapid growth of markets and stimulating quantitatively oriented minds. But, with time, its simplicity became a liability — and yet its legacy persists.